Rigorous 2D Model for Study of Pulsed and Monochromatic Waves Propagation Near the Earth’s Surface - Seil S. Sautbekov; Yuriy K. Sirenko; Nataliya P. Yashina; Aleksey A. Vertiy (International Journal of Antennas and Propagation)
A model problem considered in the paper allows solving rather complex 2D problems of the electromagnetic wave propagation with a required accuracy using conventional personal computers. The problems are of great importance for the theory and practical applications. The association of FDTD schemes with exact absorbing conditions makes up the basis for constructing models of the kind. This approach reduces the original open initial boundary value problems to the equivalent closed problems which can be solved numerically using the standard grid methods.